Pengaruh Penerapan Prinsip Good Corporate Governance Terhadap Kinerja Keuangan pada PT Perkebunan Nusantara VI (PTPN 6) - Fairuz Putra Anvy; Netty Herawaty; Rahayu Rahayu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The background of the problem is whether or not the implementation of good corporate governance principles has an impact on financial performance at PT Perkebunan Nusantara VI (PTPN 6). This study uses a quantitative approach with a descriptive research type. In the context of this study, primary data was collected through direct questionnaire distribution to respondents at PT Perkebunan Nusantara VI (PTPN 6). The selection of data collection methods through questionnaires with closed questions is expected to assist researchers in collecting relevant and reliable data related to the influence of transparency, independence, accountability, responsibility, and fairness on financial performance at PT Perkebunan Nusantara VI (PTPN 6). In this study, the population used was all employees of PT Perkebunan Nusantara VI (PTPN 6) recorded in the personnel data as of October 2024, totaling 257 people. The analysis used in this study is descriptive statistical analysis. Research Instrument Tests include validity tests and reliability tests. Before conducting regression and correlation analyses, it is important to conduct classical assumption tests. Linear regression analysis is a method used to examine how changes in the dependent variable are affected by fluctuations in two or more independent variables. Hypothesis tests include the t-test, F-test, and R2 test. Based on the analysis and discussion regarding the impact of the implementation of good corporate governance principles on financial performance at PT Perkebunan Nusantara VI (PTPN 6),